Economic vulnerability and payment for research participation. (June 2020) - Gelinas, Luke; White, Sarah A; Bierer, Barbara E
There has been significant analysis of the ethical and regulatory issues involved with paying research participants, but less attention has been focused specifically on paying economically vulnerable individuals and the unique challenges it may present. This is important, as individuals of lower socio-economic standing are present in all disease groups and study populations. Moreover, clinical research is often conducted in economically under-developed locales, such as lower- or middle-income countries as well as impoverished locales of otherwise wealthy nations (such as, for example, rural Appalachia in the United States). Is it ethical to offer payment in such contexts? What are the ethical considerations relevant for determining payment rates and practices to individuals who are economically vulnerable? We offer an analysis of these issues, focusing on four unique areas of concern: (1) whether the risk of undue influence is greater for economically vulnerable individuals than for wealthier ones; (2) whether payment unacceptably raises the risk of 'unjust influence' or disproportionate representation of poor people in clinical research; (3) the positive reasons in favor of paying economically vulnerable people that stem from the ethical value of fairness; and (4) appropriate compensation rates for economically vulnerable populations. Our analysis supports the position that payment to economically vulnerable populations is ethically justified and indeed desirable when certain conditions are met.